The concept of human capital: the core system in lifelong learning (LLL) among repeated offenders for drug abuse in Kelantan / Zanirah Mustafa@Busu ... [et al.] - Mustafa@Busu, Zanirah; Nik Din, Nik Muniyati; Ismail, Mohd Khairul Anwar; Mat Zin, Mohd Nazri; Che Mat, Che Bakar; Mohd Firdaus Kozako, Intan Nurul 'Ain (Universiti Teknologi MARA, 2021)
Drugs have become a big threat to the country. For the development of our country, the increase in the number of inmates in prisons in Malaysia is something to be concerned about. It affects the development of the economy, education, and health. Apart from the increasing number of prisoners in jail, an increase in recidivism cases among prisoners in Malaysia is also alarming. This indicates that prisoners are undaunted when committing the crimes and lack of spirituality to help them to face the challenges after being released from prison. The aim of this study is to examine and identify the concept of human capital that is suitable for the formation of the Life long Learning Model in terms of spiritual guidance to ex-offenders for drug abuse. Furthermore, the study also aims to test and analyze the extent to which the level of understanding of Islam among the drug offenders in Malaysia and generate a Lifelong Learning Model based on the concept of human capital in terms of spiritual guidance. The study adopts qualitative methods by using a descriptive study which is based on the existing scenarios. The data is collected from library sources including research on relevant documents, and observation. Therefore, this study also utilize da survey that aimed at studying the implementation of a lifelong learning model through the development of a human capital conceptual frame work for ex-offender of drug abuse. Thus, a study is needed to develop and produce a new model which is a lifelong learning model based on the human capital concept that focuses on spiritual development and guidance specifically for ex-offenders of drug abuse to address the increasing frequency of repeated offenses in Malaysia. This study provides a significant impact on the prisoners themselves, their families, communities, and the country.